Deciphering intercellular communication in the cerebellar external granule layer: Insights into non-classical connections in neural development - Malalaniaina Rakotobe; Shiyu Liu; Garima Virmani; Gabriel Kaddour; Nathaly Dongo Mendoza; Frédéric Doussau; Jean Livet; Laurence Cathala; Chiara Zurzolo (PLoS ONE, 2026)
Intercellular communication is essential for brain development. While classical modes—paracrine, juxtacrine, and synaptic signaling—are well characterized, emerging evidence suggests that membranous bridges, such as tunneling nanotubes (TNTs), forming de novo between cells and mainly described in vitro , may also contribute. Yet their presence and function in vivo remain unclear, partly due to the difficulty of distinguishing them from other intercellular connections (ICs). Building on connectomic observations in fixed tissue reporting ICs in the external granule layer (EGL) of the developing cerebellum, we examined their nature in postnatal day 7 (P7) mice. Using immunofluorescence, sparse genetic labelling, and live imaging, we distinguished division-independent ICs from cytokinetic bridges (CBs) and intercellular bridges (IBs). CBs were detected in the EGL, whereas IBs were not observed in this region. In addition to CBs, we identified membranous protrusions which appeared to link clonally and non-clonally related cells. The presence of these ICs reinforces previous connectomic evidence in fixed tissue and raises the possibility that they may participate in intercellular communication during cerebellar development. These findings warrant further investigation into a potentially underexplored mode of communication in the developing brain.